PERANCANGAN ANTENA 5/8λ BERPOLARISASI CIRCULAR PADA BAND VHF (30-300 MHz) - Yuli Christyono; Imam Santoso; Budi Setiawan (Transmisi: Jurnal Ilmiah Teknik Elektro, 2010)
Since Hertz and Marconi, antennas have became increasingly important to our society until now they are indispensable. They are everywhere: at home and workplaces, on cars and aircraft, also in ships and satellites. So far most used antenna is an antenna with a single polarization, the horizontal polarization or vertical polarization only. The advantage of circular polarization is the radiation of antenna can be well received by the vertical receiving antenna or horizontal receiving antenna. The purpose of this research is to design and build a circular polarized antenna. Then the values of the parameters measured using Hewlett Packard 8656B Signal Generator as a transmitter and Hewlett Packard 8901A Modulation Analyzer as a receiver. Both measuring devices were used to determine the frequency and power generated by the antenna. SX-1000 SWR meter as a measuring VSWR and analog VU meters are used to determine the signal strength of the antenna. The result shows that the antenna works well on a predetermined frequency (144 MHz), has omni directional radiation pattern and its VSWR is 1.09. The result of the antenna radiation can also be well received, using vertical and horizontal polarization antenna. VU meter shows that the highest value when antenna used as transmitter is 10 μV and 11 μV when antenna is used as receiver antenna. Keywords: Antenna, vertical polarization, horizontal polarization, circular polarization.